Entre o jornal escolar e as memórias: cultura e identidade do Ginásio Salesiano Dom Bosco (1951‒1955) - Schweter, Isis Sanfins (2022)
This research aims to look into the school culture and the identity of Ginásio Salesiano Dom Bosco in Piracicaba (Sao Paulo). It is intended to carry out this investigation through the analysis of some editions of the school newspaper A Voz do Dom Bosco: conducted by its students, which was published between 1951 and 1955, as well as memorial publications related to the history of this institution. The school newspaper and the production of Salesians’memoirs are components of the institution's materiality and reveal aspects of the school's own identity. The main sources for this research are composed of 20 newspaper A Voz do Dom Bosco’s editions; in addition, an institutional publication celebrating the institution's 50th anniversary and records of individual memories of people who passed through the school in that context. The theoretical framework of this work is the propositions of Dominique Julia (2001) on the concept of school culture and the theoretical-methodological perspective of Magalhães (2004) regarding the meso-approach to the study of the history of educational institutions. In relation to the conceptual framework of the school newspaper, the propositions of Amaral (2013), Bastos and Ermel (2013) were considered to understand the newspaper: on the one hand, as educational practices of the institution; on the other, as revealing elements of their customs and values in a historical perspective. For the methodological analysis of individual and collective memories, the reference of Pollack (1992), Magalhães (2004), on the institution's legitimized memory, and Seixas (2001), referring to voluntary memories, was used. The hypothesis to be investigated is that the school newspaper A Voz do Dom Bosco appears as an activity supervised by the institution's managers and not as a private initiative of the students, presenting a contradiction between the New School educational prescriptions of both Freinet (the 1920s and 1930), in France, as well as by Guerino Casassanta (1939), in Brazil, approaching the perspective of school auxiliary associations, analyzed by Bastos and Ermel (2013) and Rabelo (2013). Members of the Salesian Congregation of Piracicaba (SP) published memorial works with the aim of framing and solidifying a given collective memory of this group in the space of the city and the institution. The individual memorialistic publications contributed to reinforcing the framework of this memory. In turn, the school newspaper and the individual memories served as a vehicle to reinforce the memory of the Congregation in the city and to convey, through the editions, the educational, political, and religious values of this group. Furthermore, to reveal aspects of the Salesian pedagogical project, which was verified through the appropriation relationship, carried out by the editors of the school newspaper about the regulations of the Salesian Houses, prescriptions of the 19th century elaborated by the founder of the Order, the parish priest Don Bosco